Bacteroides forsythus: sensitivity to antimicrobial agents in samples from patients with periodontitis (Pesquisa Odontológica Brasileira, 2001)
An in vitro antimicrobial sensitivity test (technique of agar dilution) was carried out for 105 clinical isolates of B. forsythus from patients with periodontitis. Metronidazole and amoxicillin were the most efficient drugs and, thus, are indicated for the treatment of periodontal infections in which this microorganism is the most prevalent pathogen.